STUDYING THE CRITERIA FOR CREATION OF SPEECH ACTIVITY OF ENGLISH STUDENTS (Web of Teachers: Inderscience Research, 2023)
In this article we aim to discuss some relevant ideas for having effective and helpful activities to reach higher speaking level. Firstly, we should know the purpose of speaking activity what we want to focus on, fluency or accuracy? We need to keep these questions in mind when preparing a speaking task.